Seroconversión de expuestos perinatales que recibieron profilaxis materno-infantil nacidos en el Hospital Teofilo Dávila desde el año 2010-2013. - Romero Chuquimarca, Johanna (2015)
Pregnant with reactive test for HIV and antiretroviral treatment during this stage, decreases the chances of vertical transmission, but after birth the infant received antiretroviral therapy and it is likely that the year six months this child present seroconversion.